Edukasi pada Remaja Sebagai Peningkatan Pengetahuan dan Pencegahan Perilaku Seksual Berisiko di Madrasah Aliyah Negeri (MAN) Padusunan Kota Pariaman Tahun 2024 - Rosmi Eni; Hasmita Hasmita; Miswarti Miswarti; Jufrika Gusni; Yanti Nopita (Jurnal Nusantara Berbakti, 2024)
Risky sexual behavior among adolescents is a very complex problem, especially for unmarried adolescents, so it worries parents, educators, the government and other experts and becomes the world's spotlight. Stepping on the teenage years, the desire for teenage lust begins to develop, for that teenagers must learn to adapt to all the rules of culture, mores that exist in society. On this occasion, activities the service in 2022 is carried ut at one of the State Aliyah Madrasah schools Pariaman City. This time the dedication activity raised the theme of Education for teenagers. They are given education to be able to increase their knowledge regarding risky sexual behavior in order to avoid disgraceful actions that destroy their future because this is the teenage period, a period that is very vulnerable and easily fall into due to their lack of knowledge